SUBSTANTIATION FOR PRINCIPLES OF AESTHETIC STOMATOLOGY - I.K. Lutskaya (Український стоматологічний альманах)
A scope of results by global dental practice bears testimony to the fact, that there is an urgent necessity to work out and formulate the basic principles, standards and definitions of aesthetic Stomatology as a study, which in its turn ensures wide implementation of prospective patterns and methods into the healthcare system.